Make A Match Learning Model on Learning Outcomes in Elementary Schools: A Bibliometric Analysis - Muslikah, Aliyah; Amriyah, Chairul; Ningrum, Ayu Reza (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This article will map the architecture and detect trends in scholarly papers on the Make a Match (MaM) Learning Model in Elementary Schools from 2020 to 2025. The goals of this study are to examine annual publication growth, identify the most prolific journals, map significant keyword networks, and detect new topic trends in this literature. The study employed bibliometrics. Data were obtained using Publish or Perish software from Google Scholar, Crossref, and OpenAlex by searching the keywords